Validación del método elisa para la determinación cuantitativa de antígeno prostático específico como prueba diagnóstica en el laboratorio Quintanilla S.R.L. de la ciudad de Trujillo - Valencia Valera, Daniel Antonio (2006)
In the present assay it was investigated if method ELISA for the determination of prostate specific antigen (PSA) employee in the Quintanilla Laboratory S.R.L. fulfills the validation criteria. For this the following parameters were evaluated: linearity, precision (repeatability and reproducibility), exactitude, detection and quantification limits and robustness, which were determined according to the established by the Spaniard Association of Pharmacists of the Industry and following the procedures described in the inserted of kit of reagents provided by the manufacturer "DIAGNOSTIC AUTOMATION INC". The results of the study show us that the calibration chart was linear with a correlation coefficient equal to 0.998; the statistical test of the slope confirmed the linearity. The variation coefficient in repeatability assay was 4.604% and in the case of the reproducibility assay it was 4,432%. The exactitude of the method was demonstrated after applying the t-student test with 95% of confidence and 8 degrees of freedom and obtaining a t - experimental value (1.541) smaller to t – distribution table value (2.306). The detection and quantification limits were 0,272ng/mL and 0,908ng/mL respectively. The method turned out to be robustness to the variation of analysts and ends for micropipettes more do not to the case of temperature variation. This way, is demonstrated that the method fulfills the validation criteria